Piezoelectric activity of relaxor-PbTiO(3) based single crystals and polycrystalline ceramics at cryogenic temperatures: Intrinsic and extrinsic contributions - Li, Fei (American Institute of Physics, 2010)
The piezoelectric activity in [001] poled Pb(In(1∕2)Nb(1∕2))O(3)–Pb(Mg(1∕3)Nb(2∕3))O(3)–PbTiO(3) crystals was investigated as a function of composition and temperature. The level of intrinsic and∕or extrinsic contribution to the total piezoelectric activity was analyzed using Rayleigh method. The results revealed that though 95% of the observed piezoelectric activity in rhombohedral crystals was intrinsic (lattice), the properties decreased significantly with decreasing temperature. At −150 °C, the piezoelectric response decreased by 40%–55% for the compositions close to a morphotropic phase boundary (rhombohedral-monoclinic or monoclinic-tetragonal), while decreasing only 20%–30% for the compositions in the rhombohedral region. The piezoelectric properties of Pb(Mg(1∕3)Nb(2∕3))O(3)–PbTiO(3) polycrystalline ceramics were found to decrease by 75%, showing both intrinsic and extrinsic contributions play important role in the reduction in piezoelectricity at cryogenic temperatures for ceramics.